Factors Influencing the Incidence of Anemia Among Pregnant Women at Pasar Merah Community Health Center, Medan City - Anita Sari; Novita Andriani Br Manjorang; Siti Ramadani; Bunga Aulia; July Rosa Samosir (Universitas Pahlawan Tuanku Tambusai, 2026)
Anemia during pregnancy remains a major public health problem because it increases the risk of maternal and fetal complications, including miscarriage, preterm delivery, postpartum hemorrhage, low birth weight, and maternal and neonatal mortality. Maternal age, parity, and gestational age are among the factors commonly associated with the occurrence of anemia in pregnant women. Objective to analyze the influence of maternal age, parity, and gestational age on the incidence of anemia among pregnant women in the working area of the Pasar Merah Community Health Center, Medan Kota District, Medan City, North Sumatra Province, in 2026. Methods this study used a quantitative analytic design with a cross-sectional approach. The study was conducted at Pasar Merah Public Health Center, Medan City, North Sumatra, in 2026. The population consisted of pregnant twomen attending antenatal care (ANC), and samples were selected using purposive sampling. The independent variables were maternal age, parity, and gestational age, while the dependent variable was the incidence of anemia. Data were collected from medical records and analyzed using univariate and bivariate analyses with the Chi-square. Results a total of 35 pregnant women participated in this study. Most respondents were aged 20–35 years,had multiparity, and were in the second and third trimesters of pregnancy. Conclusion the findings indicate that maternal age, parity, and gestational age influence the occurrence of anemia during pregnancy. Pregnant women aged >35 years, those with higher parity, and women in the third trimester had a greater risk of developing anemia due to increased iron requirements and physiological changes during pregnancy. These findings support previous studies emphasizing the importance of routine antenatal care, iron supplementation, and nutritional counseling to prevent anemia.